2015
DOI: 10.18632/oncotarget.6274
|View full text |Cite
|
Sign up to set email alerts
|

Social inequalities and cancer: can the European deprivation index predict patients' difficulties in health care access? a pilot study

Abstract: ContextThe European Deprivation Index (EDI), is a new ecological estimate for Socio-Economic Status (SES). This study postulates that Time-To-Treatment could be used as a cancer quality-of -care surrogate in order to identify the association between cancer patient's SES and quality of care in a French comprehensive cancer center.Methodsretrospective mono-centered cohort study. All consecutive incoming adult patients diagnosed for breast cancer(BC), prostate cancer(PC), colorectal cancer (CRC), lung cancer(LC) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 42 publications
(38 reference statements)
2
22
0
1
Order By: Relevance
“…Surprisingly, surgical treatment received did not further explain differences in the excess hazard in either group, where previously this has been shown to be influential [8]. Additionally, time to surgery was not found here to improve the fit of any of the models for the screen-detected group, similar to the findings of a recent smaller study [25]. However, the measure available was not very discriminatory, partly because almost all women had surgery, but also because information on hormone therapy, chemotherapy and radiotherapy were too incomplete to use.…”
Section: Discussionsupporting
confidence: 86%
“…Surprisingly, surgical treatment received did not further explain differences in the excess hazard in either group, where previously this has been shown to be influential [8]. Additionally, time to surgery was not found here to improve the fit of any of the models for the screen-detected group, similar to the findings of a recent smaller study [25]. However, the measure available was not very discriminatory, partly because almost all women had surgery, but also because information on hormone therapy, chemotherapy and radiotherapy were too incomplete to use.…”
Section: Discussionsupporting
confidence: 86%
“…No studies were found on the relationships between SES and surgical outcomes, post-surgical complications, length of stay and waiting times in diagnosis and treatment stages which are used as surrogates for the quality of treatment received. These issues have been reported internationally [ 3 , 86 , 95 ] and need to be explored further.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, for the first time in Italy, we linked population-based data with information on care and treatment to the census tract DI database [ 33 ], in order to attribute to each cancer case a SES category. A limitation of our study regards the use of a census tract DI rather than an individual DI because, as argued by Moriceau et al [ 34 ], the association between SES and cancer survival, where it exists, was stronger when SES was assessed individually [ 35 ] than according to the census tracts [ 36 ]. Indeed, people can live in a deprived area without being deprived themselves.…”
Section: Discussionmentioning
confidence: 99%